ANALISIS FAKTOR INTERNAL KESULITAN BELAJAR MATEMATIKA KELAS V DI SEKOLAH DASAR QUR’AN AL- MUWAFFAQ KABUPATEN TANGERANG - Luthfiah Nur Fadilla; Nelly Manik; Muhammad Azdi (STKIP Subang, 2023)
Learning mathematics is one of the subjects that students are less interested in. One of the reasons is that mathematics is a subject that is difficult to understand or understand. The low interest of students in learning mathematics causes low student learning scores in mathematics. This study aims to determine the factors that cause learning difficulties in fifth grade students. The method used in this research is descriptive qualitative using data collection techniques in the form of kuesioner interviews. and documentation. Checking the validity of the data using triangulation. Data is analyzed through the steps of data collection, data reduction, data presentation, and drawing conclusions. The subjects in this study were students and teachers of class V with a total of 16 respondents, namely teachers of class V and students of class V. Based on the results of the study it was found that there were factors of learning difficulties in mathematics that caused low student learning scores.